Interaction of Neurovascular Signals in the Degraded Condylar Cartilage - Qin, Wenpin; Zhang, Zibin; Yan, Jianfei; Han, Xiaoxiao; Niu, Li-Na; Jiao, Kai (Frontiers in Bioengineering and Biotechnology, 2022)
Introduction: Degradation of the condylar cartilage during temporomandibular osteoarthritis (TMJ-OA) results in the infiltration of nerves, blood vessels and inflammatory cells from the subchondral bone into the cartilage. The interaction among innervation, angiogenesis and inflammation in the condylar cartilage of TMJ-OA remains largely unknown. Method: In the present study, microarray-based transcriptome analysis was used to detect, and quantitative real-time polymerase chain reaction was used to validate transcriptome changes in the condylar cartilage from a well-established rat TMJ-OA model. Gene ontology (GO), Kyoto encyclopedia of genes and genomes (KEGG) pathway and protein-protein interaction (PPI) analyses were conducted. Result: There were 1817 differentially expressed genes (DEGs, fold change ≥ 2, p < 0.05) between TMJ-OA and control cartilages, with 553 up-regulated and 1264 down-regulated genes. Among those genes, representative DEGs with known/suspected roles in innervation, angiogenesis and inflammation were further validated by enriched GO terms and KEGG pathways. The DEGs related to innervation were predominately enriched in the GO terms of neurogenesis, generation of neurons, and KEGG pathways of cholinergic synapse and neurotrophin signaling. Genes related to angiogenesis were enriched in GO terms of vasculature and blood vessel development, and KEGG pathways of hypoxia-inducible factor 1 (HIF-1) pathway and calcium signaling pathway. For inflammation, the DEGs were enriched in the GO terms of immune system process and immune response, and KEGG pathways of Toll-like receptor and transforming growth factor β (TGFβ) signaling. Analysis with PPI indicated that the aforementioned DEGs were highly-interacted. Several hub genes such as v-akt murine thymoma viral oncogene homolog 1 (Akt1), glycogen synthase kinase 3β (Gsk3b), fibroblast growth factor 2 (Fgf2) and nerve growth factor receptor (Ngfr) were validated. Conclusion: The present study demonstrated, for the first time, that intimate interactions exist among innervation, angiogenesis and inflammation in the condylar cartilage of TMJ-OA.